139k views
4 votes
Pls help solve with work!

Pls help solve with work!-example-1

1 Answer

2 votes

Answer:

- 22

Explanation:

(g - f)(- 4) , means evaluate g(x) - f(x) when x = - 4

g(x) - f(x)

= 3x + 3 - (x² - 3) ← distribute by - 1

= 3x + 3 - x² + 3 ← collect like terms

= 3x - x² + 6 ← substitute x = - 4 into expression and evaluate

= 3(- 4) - (- 4)² + 6

= - 12 - 16 + 6 = - 28 + 6 = - 22

User Shimano
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.